2011
DOI: 10.3109/14767058.2011.575905
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal maternal body mass index and obstetric and neonatal outcome

Abstract: Severe or morbid obesity were associated with an increased risk of adverse perinatal outcome and mortality and should be managed as high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 24 publications
4
26
1
Order By: Relevance
“…However, the findings have not been consistent. Galan and colleagues, 19 in a retrospective cohort study, reported that women with class II or III obesity (BMI 35 or higher) were more likely to have an umbilical artery pH less than 7.10 than were normal-weight women (adjusted odds ratio 2.15, 95% CI 1.05-4.38). In contrast, Maisonneuve and colleagues, 20 in a case-control study, reported that cases (umbilical artery pH less than 7.00) were more likely to be obese (BMI 30 or higher) than controls, but the difference did not remain statistically significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the findings have not been consistent. Galan and colleagues, 19 in a retrospective cohort study, reported that women with class II or III obesity (BMI 35 or higher) were more likely to have an umbilical artery pH less than 7.10 than were normal-weight women (adjusted odds ratio 2.15, 95% CI 1.05-4.38). In contrast, Maisonneuve and colleagues, 20 in a case-control study, reported that cases (umbilical artery pH less than 7.00) were more likely to be obese (BMI 30 or higher) than controls, but the difference did not remain statistically significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%
“…There is no uniformly agreed-on threshold for defining acidemia. Although an arterial cord pH of 7.10 is approximately two standard deviations below the mean and others have used this threshold, 19 most neonates with values more extreme than even more restrictive thresholds (eg, arterial pH less than 7.00 or base deficit of more than 16 mmol/L) do not have complications associated with acidemia. Therefore, we refer to "adverse acid-base status" or "lower pH and higher base deficit" throughout the article rather than "acidemia."…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…[52][53][54][55] Perhaps most relevant to our study is the association with fetal growth restriction. 19,56 In addition, obesity is linked to chronic illnesses 57,58 and social disadvantage, 59 which might affect the mother-infant interaction and the resources available to enhance the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are very few studies focusing on Mediterranean population and pregnancy outcome concerning offspring's death in obese pregnant women [12,30].…”
Section: Introductionmentioning
confidence: 98%